Geopolityczna analiza potêgi w subregionie Zatoki Perskiej - Grabowski, Wojciech (Przegląd Strategiczny, 2014)
The sub-region of the Persian Gulf, being rich in oil and gas, has become an object of rivalry between regional and global influences. If the countries want to compete effectively though, they need to have power. This article analyzes the elements that comprise the power in the Persian Gulf, which is necessary to understand contemporary balance of power in this region. Analysis is based on the triad of American political scientist – Joseph Nye, who has distinguished soft, hard and smart power. Consequently, the author of the article has presented not only the current balance of power, but also potential balances in the sub-region. There is also an attempt to find an answer to the question: which of these balances of power would be the safest for the Persian Gulf?